Manganese2+-doped copper tin telluride absorber layer-sensitized solar cells - Panupong Sangsuriyawong (2018)
© 2018 American Scientific Publishers. Manganese 2+ -doped copper tin telluride nanoparticles (Mn 2+ :Cu 2 SnTe 3 NPs), as an absorber layer, were grown using a chemical bath deposition (CBD) technique and demonstrated for solar cell applications. The cubical structure was formed on the WO 3 surface with the band gap (Eg) of Cu 2 SnTe 3 NPs decreased from 1.80 to 1.67 eV after Mn 2+ doping. The photovoltaic property at 1 sun shows the efficiency (η) of 0.276%. The η was increased with reducing sunlight intensity due to the lower carrier recombination process at an electrode and electrolyte interface, which leads to the increasing η. The highest η of 1.120% was yielded at 0.1 sun with a J sc = 2.81 mA/cm 2 , a Voc = 0.148 V, a FF = 26.8%. It can be noted that this kind of material and a synthesis procedure can be feasibly further improved for a higher efficiency and more stability on an absorber layer.